2012
DOI: 10.3109/00365521.2011.647412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver fibrosis by transient elastography (Fibroscan®) in patients with inflammatory bowel disease treated with methotrexate: a multicentric trial

Abstract: (1) Development of advanced liver fibrosis in IBD patients treated with methotrexate is exceptional. (2) There were no differences in liver stiffness depending on the type of IBD or the cumulative dose of methotrexate. (3) FibroScan® may be potentially useful for evaluation and follow-up of liver fibrosis in methotrexate-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 24 publications
3
32
0
2
Order By: Relevance
“…Despite the fact that the reliability of TE as a surrogate marker of liver fibrosis has only been validated in the Hepatitis C scenario, and that we could not perform TE in all patients included, it is clear that the presence of biochemical hepatotoxicity is not a reliable marker for liver damage in patients under treatment with methotrexate. Taking these facts into account, it seems reasonable to consider that the proportion of patients with methotrexate-induced liver damage may be greater than expected, although it seldom seems to be a clinically relevant issue, and that TE may be potentially useful for the evaluation and follow-up of liver fibrosis in methotrexate-treated IBD patients, as has been proposed in a recent cross-sectional study [29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the fact that the reliability of TE as a surrogate marker of liver fibrosis has only been validated in the Hepatitis C scenario, and that we could not perform TE in all patients included, it is clear that the presence of biochemical hepatotoxicity is not a reliable marker for liver damage in patients under treatment with methotrexate. Taking these facts into account, it seems reasonable to consider that the proportion of patients with methotrexate-induced liver damage may be greater than expected, although it seldom seems to be a clinically relevant issue, and that TE may be potentially useful for the evaluation and follow-up of liver fibrosis in methotrexate-treated IBD patients, as has been proposed in a recent cross-sectional study [29].…”
Section: Discussionmentioning
confidence: 96%
“…With respect to the well-known good reliability and correlation between the liver stiffness measured by TE and the grade of liver fibrosis detected by liver biopsy in the chronic hepatitis C scenario, the results of the TE measurements have been presented in grades of histological fibrosis according to the commonly used METAVIR scoring system [16,28] to make them easy to understand. The cutoff values for each stage of hepatic fibrosis (METAVIR scoring system) were established according to the literature, choosing the values with the best sensitivityspecificity ratio; considering that there are no studies that establish specific cutoff values for hepatic fibrosis in patients treated with methotrexate and that the most reliable data come from studies including patients with chronic hepatitis C, other previously reported studies, as well as our study, use the cutoff values established by those trials and the METAVIR scoring system to express the grade of fibrosis on a five-point scale from 0 to 4 [29][30][31]. The cutoff values were F Z 2 : 7.1 kPa, F Z 3 : 9.5 kPa, and F Z 4 : 12.1 kPa.…”
Section: Methodsmentioning
confidence: 98%
“…Due to this disparity, Society's guidelines differ on how patients on MTX should be monitored to prevent MTXinduced liver fibrosis [115,116] . Although liver biopsy is still suggested in these patients in case of persistent elevation of transaminase after drug discontinuation, and for ruling out other potential cause of chronic liver disease, there is robust evidence that Fibroscan Elastography may become in a near future the gold standard for fibrosis investigation in patients treated with MTX [117,118] . Most studies concluded that MTX therapy is safe, and that Fibroscan is useful for monitoring liver fibrosis in patients treated with this drug.…”
Section: Association Of Sle With Drug-induced Hepatotoxicitymentioning
confidence: 99%
“…En las EII disponemos de un metaanálisis reciente, en el que si se medía la hepatotoxicidad por la hipertransaminasemia (> x2 el valor normal), su incidencia era de 0,9 pacientes/mes, con una tasa de retirada del tratamiento de 0,8 pacientes/mes 62 63 . Los datos de seguimiento con elastografía también muestran una frecuencia baja de toxicidad a largo plazo 64 . Un análisis de la experiencia pediá-trica, sin embargo, señala una probabilidad mucho mayor de desarrollo de hepatotoxicidad, que se encuentra en uno de cada 10 pacientes, lo que con cierta frecuencia llevó a una disminución de la dosis (6%) o a una retirada del fármaco (4,5%) 65 .…”
Section: Toxicidadunclassified
“…En los primeros tres meses se llevará a cabo una analí-tica mensual, y si el fármaco es bien tolerado se pasará a un control cada 3 meses durante 2 años, y posteriormente el control se podrá hacer cada 4 a 6 meses. Como la correlación entre las alteraciones analíticas y la presencia de lesiones hepáticas es muy pobre 63,86 , si se dispone de elastografía parece razonable llevarla a cabo con periodicidad, en caso de tratamientos prolongados, tal vez cada dos años a partir de los 5 primeros; realizándose una biopsia solo en el caso de que la elastrografía y/o los datos analíticos lo aconsejen 64 . No se llevarán a cabo radiografías de tórax por control rutinario, pero sí si aparece sintomatología.…”
Section: Seguimientounclassified